The awareness of thyroid disorders and an iodine-rich diet among a sample of the population in some western cities of Libya - Abuhlega, Thuraya; Shtewi, Hanan; Alhammali, Malak; Farhat, Narges; Algelani, Fatima (Journal of Pure & Applied Sciences, 2024)
The deficiency of iodine in a diet is a global health issue. Therefore, this study aimed to assess the awareness of thyroid disorders and explore iodine-related dietary knowledge and practices among a sample of the population in some cities in western Libya. A cross-sectional survey was carried out among 425 individuals in the population, of whom 265 were healthy and 160 had thyroid disorders. The sample consisted of 72.0% females and 28.0% males. More than a quarter of the sample (26.6%) were between the ages of 38 and 47. The data were analyzed by SPSS. The findings revealed that only 37.9%, 43.8%, and 46.9% of the respondents knew that thyroid dysfunction causes brain damage, iodine is the main cause of thyroid problems, and thyroid disorders are genetic, respectively. As well, almost one-third of respondents (33.0%) expected that the mothers' thyroid problems would cause harm to the fetus. Only 14.6% of respondents realized that the function of the thyroid gland is important for metabolism. The findings also revealed that only 33.4% of respondents knew the main dietary sources of iodine. As well, only 23.5% of respondents ate seafood two or three times a week. Very few of the respondents (8.90%) used iodized salt. The study indicated that there is a need to raise awareness of thyroid disorders and their relationship with food among the population in western Libya. Therefore, effective and continuous programs from responsible authorities are essential.